Rhein Relieves Oxidative Stress in an Aβ1-42 Oligomer-Burdened Neuron Model by Activating the SIRT1/PGC-1α-Regulated Mitochondrial Biogenesis - Yin, Zhihui; Geng, Xinyue; Zhang, Zhengyi; Wang, Ying; Gao, Xiaoyan (Frontiers in Pharmacology, 2021)
Neuronal mitochondrial oxidative stress induced by β-amyloid (Aβ) is an early event of Alzheimer’s disease (AD). Emerging evidence has shown that antioxidant therapy represents a promising therapeutic strategy for the treatment of AD. In this study, we investigated the antioxidant activity of rhein against Aβ1-42 oligomer-induced mitochondrial oxidative stress in primary neurons and proposed a potential antioxidant pathway involved. The results suggested that rhein significantly reduced reactive oxygen species (ROS) level, reversed the depletion of mitochondrial membrane potential, and protected neurons from oxidative stress-associated apoptosis. Moreover, further study indicated that rhein activated mitochondrial biogenesis accompanied by increased cytochrome C oxidase (CytOx) and superoxide dismutase (SOD) activities. CytOx on the respiratory chain inhibited the production of ROS from electron leakage and SOD helped to eliminate excess ROS. Finally, western blot analysis confirmed that rhein remarkedly increased the protein expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) together with its upstream deacetylase sirtuin 1 (SIRT1), and activated downstream transcription factor nuclear respiratory factor 1, promoting mitochondrial biogenesis. In conclusion, our results demonstrate that rhein activates mitochondrial biogenesis regulated by the SIRT1/PGC-1α pathway as an antioxidant defense system against Aβ1-42 oligomer-induced oxidative stress. These findings broaden our knowledge of improving mitochondrial biogenesis as an approach for relieving neuronal oxidative stress in AD.